Carte du Bassin du Mackenzie, dressée de 1862 à 1873 / par E. Petitot, Missionnaire Oblat de Marie I. - Petitot, Emile Fortune? Stanislas Joseph, 1838-1917 (1875)
Shows explorers' routes, missions, forts, geology and names and locations of indiginous tribes.; Relief shown by hachures and spot heights.; Includes inset of "Lac de Genève à l'échelle de la Carte."; Originally folded in text: "Géographie de l'Athabaskaw-Mackenzie et des Grands Lacs du Bassin Arctique" (148 p. : maps (one fold., part. color) charts 23 cm.); "Bulletin de la Société de Geographie" -- upper left margin. Color 1:2,100,000